(3QSGdI aj CMcGe GdeQVis - (3CMeO EHQGgje Hf Ndjds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi GdPj dG jcda faSG EdG hSYgG aEf GdYHO GdabjQ CMeO Hf EHQGgje Hf Ndjd jbhd (B: (3deG cfJ aj Ref HYV GdeaJjf eCehQG HJUhjQ GdaJGhi hJKHjJgG hJShjO GdhGbYGJ hJHjjVgG hcGf Pdc HGYKG dJJHY GdcJH ef GdNdGUI hGdYeGOjI hZjQgeG hCMcGe GdeQVi hEf cGfJ eHfjI aj Jdc GdaUhd hGdCHhGH dcf WdHgG efgG dG jNdh ef GdJYH hGdGQJjGH CQOJ Cf CLeYgG Ydi JQJjH djSgd GdWdHs
(3BNQgG (B:s
(3hbO fbdfG cPdc ef bHd ef aUhd GdYeGOj (B: (3dG jedc GdOGjf EKHGJ GdOjf Ydi eOjhfg GdejJ hdG Ydi GdehUi dg hdh CKHJ Ydi ef jUM EKHGJg Ydjg chUj hhGQK KHJ Mb GdGSJjaGA efgeG ef GdaUhdjf aj Pdc GdaUds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 90s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdabg GdMfHdjs